2014
DOI: 10.1108/jes-08-2011-0092
|View full text |Cite
|
Sign up to set email alerts
|

Does regional currency integration ameliorate global macroeconomic shocks in sub-Saharan Africa? The case of the 2008-2009 global financial crisis

Abstract: Purpose – The purpose of this paper is to consider whether regional currency integration in sub-Saharan Africa ameliorates global macroeconomic shocks by considering the impact of the 2008-2009 global financial crisis on economic growth. This suggests that Central Africa Franc Zone (CFAZ) eurocurrency union membership amplifies the effects of global business cycles in sub-Saharan Africa. Design/methodology/approach – The authors estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 37 publications
5
30
0
Order By: Relevance
“…Therefore, the impact of globalization may be more detrimental to 'economic and monetary' regions (UEMOA and CEMAC) than to purely economic regions (COMESA and EAC) 13 . This inference is consistent with documented issues of surplus liquidity in the FCFA zone (Saxegaard, 2006;Fouda, 2009) and recent findings from Price and Elu (2014) which have shown that African countries within the FCFA zone were more likely to experience credit contraction during the recent financial crisis.…”
Section: Further Discussion and Implicationssupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, the impact of globalization may be more detrimental to 'economic and monetary' regions (UEMOA and CEMAC) than to purely economic regions (COMESA and EAC) 13 . This inference is consistent with documented issues of surplus liquidity in the FCFA zone (Saxegaard, 2006;Fouda, 2009) and recent findings from Price and Elu (2014) which have shown that African countries within the FCFA zone were more likely to experience credit contraction during the recent financial crisis.…”
Section: Further Discussion and Implicationssupporting
confidence: 78%
“…Motelle and Biekpe (2015) have examined whether enhanced financial integration is the source of domestic financial sector instability to confirm the Kose et al (2011) hypothesis within the framework of the Southern African Development Community (SADC). have extended Price and Elu (2014) and Motelle and Biekpe (2015) in the context of pre-and post-crisis effects of financial globalization in domestic financial development to confirm the contemporary relevance of the debate on the rewards of liberalization.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…First, Price and Elu (2014) The present inquiry contributes to extant literature by simultaneously accounting for variations in financial development and financial globalisation in assessing the underlying hypothesis of initial financial development conditions for the reward of financial globalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Following a revival of the debate on benefits of capital account openness in financial development, some scholars have expressed deep skepticism about claims that recent financial engineering has resulted in substantial positive development externalities (Rodrik & Subramanian, 2009). This sceptical strand has been partially motivated by an evolving strand of post-crisis African development literature that is centred around the highlighted hypothesis, namely: Price and Elu (2014), Asongu (2014), Motelle and Biekpe (2015) and Asongu and De Moor (2015).…”
Section: Introductionmentioning
confidence: 99%